2022
DOI: 10.1073/pnas.2103400119
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biodiversity data suggests that mammal species are hidden in predictable places

Abstract: Significance Only an estimated 1 to 10% of Earth’s species have been formally described. This discrepancy between the number of species with a formal taxonomic description and actual number of species (i.e., the Linnean shortfall) hampers research across the biological sciences. To explore whether the Linnean shortfall results from poor taxonomic practice or not enough taxonomic effort, we applied machine-learning techniques to build a predictive model to identify named species that are likely to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 194 publications
1
41
2
Order By: Relevance
“…Studies using data from our initial data aggregation pipelines have further demonstrated the utility of single‐locus large‐scale studies that also utilize data layers from other sources. Parsons et al (2022) explore cryptic diversity in mammals using molecular species delimitation methods for single‐locus data in conjunction with natural history and environmental data for over 4000 species. They found that hundreds of mammal species are still probably undescribed and that these are mostly small‐bodied taxa with large ranges (scripts for this project can be found at https://github.com/parsons463/HiddenDiversity).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies using data from our initial data aggregation pipelines have further demonstrated the utility of single‐locus large‐scale studies that also utilize data layers from other sources. Parsons et al (2022) explore cryptic diversity in mammals using molecular species delimitation methods for single‐locus data in conjunction with natural history and environmental data for over 4000 species. They found that hundreds of mammal species are still probably undescribed and that these are mostly small‐bodied taxa with large ranges (scripts for this project can be found at https://github.com/parsons463/HiddenDiversity).…”
Section: Discussionmentioning
confidence: 99%
“…We recommend individual users to capitalize on available tools for checking taxonomy when appropriate for their needs. For example, the R package taxize (Chamberlain & Szöcs, 2013) accesses many data sources to update species names, or standardized databases can be used directly to update species names such as the Mammal Diversity Database published by the American Society of Mammalogists (as in Parsons et al, 2022).…”
Section: Phylogatr Pipelinementioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that I analysed only described species for which distributional data are available. The character of the study prevented to include unrecognized, cryptic, unnamed, or unmapped species despite that they may represent a substantial component of the world's biodiversity (Parsons et al, 2022). For example, given the frequency of uncovering cryptic species through genetic analysis (Bickford et al, 2007) it is likely that many of the unsampled species will be found to harbour more taxa.…”
Section: Discussionmentioning
confidence: 99%